Bureaucratic ethics in realizing licensing services with integrity in Yogyakarta - Fitriana, Kurnia Nur; Satlita, Lena; Anggalini, Titis Dewi; Yanuardi, Yanuardi (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
Bureaucratic ethics are crucial for the integrity of licensing services at the Yogyakarta City Investment and Licensing Service. Despite challenges like corruption, collusion, and nepotism, the Yogyakarta City Government is working to institutionalize an employee code of ethics through the SATRIYA Culture and BerAKHLAK core values. This paper aims to explain the development of bureaucratic ethics in the Yogyakarta City Investment and Licensing Office, using qualitative descriptive methods such as interviews, focus group discussions, observation, and documentation. The study found that civil servants have a good understanding of bureaucratic ethics, but internalizing values and norms takes time. Efforts to achieve integrity include public interest orientation, legal certainty, equality of rights, balance of rights and obligations, professionalism, equality of treatment, openness, and accountability. However, sub-optimal results exist due to limited funds, limited public facilities, different attitudes, unintegrated coordination, and operational technical problems.